The Creative Spark: Brian Kaufman, Visual Journalist. - Kaufman, Brian (linkedin.com, 2013)
Wander around the Detroit Packard Plant with Brian Kaufman, a visual journalist whose multimedia projects help boost newspapers' relevance in the digital age.